Analisis Pemanfaatan Teknologi Digital Pada Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Di Kecamatan Tanjung Priok Jakarta Utara - Agwa, Ridha Reviana; Wulandari, Winda (Jurnal Ilmu Administrasi Publik, 2024)
This study aims to determine the utilization of digital technology on land and building tax collection in rural and urban areas in local tax revenue. Some obstacles arise when we want to make tax payments, due to home away from the Tax Office, limited time and bureaucracy and long queues in the payment process. This type of research is qualitative research. Data collection techniques using observation, interviews and documentation. Analysis techniques using data reduction, data presentation, conclusion and verification. The results showed that based on the target and the realization of tax revenue can be said to be not maximized, but the use of online systems on tax payments has begun to be effective.